The depth-distribution of nitrogen fixation by Trichodesmium spp. colonies in the tropical–subtropical North Atlantic. (October 2015) - Olson, Elise M.; McGillicuddy, Dennis J.; Dyhrman, Sonya T.; Waterbury, John B.; Davis, Cabell S.; Solow, Andrew R.
Abstract: Nitrogen fixation is an important yet still incompletely constrained component of the marine nitrogen cycle, particularly in the subsurface. A Video Plankton Recorder (VPR) survey in the subtropical North Atlantic found higher than expected Trichodesmium colony abundances at depth, leading to the hypothesis that deep nitrogen fixation in the North Atlantic may have been previously underestimated. Here, Trichodesmium colony abundances and modeled nitrogen fixation from VPR transects completed on two cruises in the tropical and subtropical North Atlantic in fall 2010 and spring 2011 were used to evaluate that hypothesis. A bio-optical model was developed based on carbon-normalized nitrogen fixation rates measured on those cruises. Estimates of colony abundance and nitrogen fixation were similar in magnitude and vertical and geographical distribution to conventional estimates in a recently compiled climatology. Thus, in the mean, VPR-based estimates of volume-specific nitrogen fixation rates at depth in the tropical North Atlantic were not inconsistent with estimates derived from conventional sampling methods. Based on this analysis, if Trichodesmium nitrogen fixation by colonies is underestimated, it is unlikely that it is due to underestimation of deep abundances by conventional sampling methods. Abstract : Highlights: Trichodesmium distribution was assessed at 10–1000 km scales with optical imaging. A bio-optical model was developed based on measured nitrogen fixation rates. Mean abundance and nitrogen fixation were consistent with climatological estimates. Spatial variations reflected temperature, salinity, stratification, and eddies.